2017
DOI: 10.3892/etm.2017.4224
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial fibrosis in congenital and pediatric heart disease

Abstract: Cardiac fibrosis is a common phenomenon in different types of heart diseases, such as ischemic heart disease, inherited cardiomyopathy mutations, diabetes, and ageing and is associated with morbidity and mortality. Increased accumulation of extracellular matrix (ECM) that impacts cardiac function, is the underlying cause of fibrotic heart disease. There are four different types of cardiac fibrosis, including, reactive interstitial fibrosis, replacement fibrosis, infiltrative interstitial fibrosis and endomyoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 57 publications
0
46
0
10
Order By: Relevance
“…The harmful stimulus induces cardiac fibroblasts to transiently express α-smooth muscle actin (α-SMA), an actin isoform that is a marker for myfibroblast and mainly responsible for the homeostasis of the ECM (Hinz et al, 2001 ). The α-SMA protein in cardiac fibroblasts is connected to the ECM through focal adhesions, and is assembled into stress fibers and remodels the surrounding ECM in response to certain types of stress, eventually causing HF (Leask, 2015 ; Tian et al, 2017 ). Although several studies have explored the origin of cardiac fibroblasts, accurate answers are still unavailable.…”
Section: Cardiac Remodelingmentioning
confidence: 99%
“…The harmful stimulus induces cardiac fibroblasts to transiently express α-smooth muscle actin (α-SMA), an actin isoform that is a marker for myfibroblast and mainly responsible for the homeostasis of the ECM (Hinz et al, 2001 ). The α-SMA protein in cardiac fibroblasts is connected to the ECM through focal adhesions, and is assembled into stress fibers and remodels the surrounding ECM in response to certain types of stress, eventually causing HF (Leask, 2015 ; Tian et al, 2017 ). Although several studies have explored the origin of cardiac fibroblasts, accurate answers are still unavailable.…”
Section: Cardiac Remodelingmentioning
confidence: 99%
“…It is a common theme in several types of heart diseases, including inherited cardiomyopathies, ischemic heart disease, diabetes and obesity, and ageing, and has been linked to morbidity and mortality [3]. During cardiac fibrosis, cardiac fibroblasts transform to a myofibroblast phenotype [3,4]. These myofibroblasts are responsible for the production of the extracellular matrix (ECM) and activation of several inflammatory pathways [5].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the interconversion of fibroblasts to myofibroblasts is prolonged. Alterations of the myocardial architecture of the injured heart contributes to impaired cardiac function and ventricular stiffness, leading to contractile dysfunction [4]. The accumulation of the ECM can also alter the mechano-electric coupling of cardiomyocytes, thereby amplifying the risk of arrhythmogenicity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The platform developed in this study allowed to evaluate the cellular structure and interactions in EMF in an in vitro model using patterns with complex microarchitectures. When comparing the results obtained from this study with those reported from pathological samples of explanted EMF tissues [52], it was found that the irregular pattern characterized by a distribution of ramifications in the tissue geometry causes more tissue remodeling for the affected area and more cardiomyocyte morphological changes than the compact pattern, generating cells agglomerations [53]. In contrast, the compact pattern presented a lower index of tissue remodeling than the irregular pattern.…”
Section: Population Countmentioning
confidence: 52%